Implementation of Group Guidance Services with Problem Solving Techniques to Improve Student Self-Efficacy - Novia Astuti (Sultan Idris Journal of Psychology and Education, 2026)
This research is motivated by the low self-efficacy of class X students at SMA Negeri 1 Teluk Batang which is shown through a lack of confidence, a tendency to avoid difficult tasks, low motivation to learn, and dependence on friends in completing academic tasks. This condition shows the need for more systematic guidance and counseling services to help increase students' self-confidence. This study aims to determine the effectiveness of the implementation of group guidance services with problem solving techniques in increasing the self-efficacy of class X students at SMA Negeri 1 Teluk Batang. The research method used is mixed methods in the form of Guidance and Counseling Action Research (PTBK) of the Kemmis and McTaggart model which includes the stages of planning, action, observation, and reflection. The study subjects amounted to 10 students who were selected using purposive sampling techniques based on low self-efficacy characteristics. Data collection techniques were carried out through observation, interviews, and psychological self-efficacy scales. The results of the study show that the application of group guidance services with problem solving techniques is able to increase students' self-efficacy as seen from increasing self-confidence, optimism, responsibility, rational thinking skills, and students' courage in facing academic tasks and problems. In addition, group dynamics help students to be more open, actively discuss, and able to learn from peer experiences. Thus, group guidance services with problem solving techniques are effectively used to increase the self-efficacy of class X students at SMA Negeri 1 Teluk Batang.